Biopotency of Avicennia marina leaf extracts against pathogenic bacteria in carp culture - M. V. N. Sravya; T. Rahul Sandeep; G. Beulah; N. S. Sampath Kumar; G. Simhachalam (AMB Express, 2025)
Abstract Disease emergence has become a main limiting factor in aquaculture. The massive application of antibiotics as disease therapy has been resulting in the adverse effects of environment, host and consumers. Ethyl acetate leaf extract of A.marina has recorded high biological activity. Crude extract has showed the antibacterial activity of range 3.2 ± 0.8 mm against B.subtilis to 5.7 ± 0.7 mm against A.hydrophila, DPPH; 15.9 ± 0.7 AAE µg/ml to 79.4 ± 1.0 AAE µg/ml and FRAP; 6.4 ± 1.3 AAE µg/ml to 127.3 ± 1.3 AAE µg/ml. The mass spectral results revealed the presence of thioacetic acid, methyl thio ethane, 1-Fluoro-2-propanone, Isopropanethiol. CAT and SOD levels of ethyl acetate extract treated fingerlings was: crude; 15.5 ± 1.0 units/mg of protein and 13 ± 0.9 units/mg of protein, purified 18.3 ± 0.5 units/mg of protein and 16.9 ± 1.1 units/mg of protein.